The Effect of Intrathecal Administration of Muscimol on Modulation of Neuropathic Pain Symptoms Resulting from Spinal Cord Injury; an Experimental Study - Marjan Hosseini; Zohreh Karami; Atousa Janzadenh; Seyed Behnamedin Jameie; Zahra Haji Mashadi; Mahmoud Yousefifard; Farinaz Nasirinezhad (Emergency, 2014)
Introduction: Neuropathic pain can be very difficult to treat and it is one of the important medical challenging about pain treatments. Muscimol as a new agonist of gamma-Aminobutyric acid receptor type A (GABAA) have been introduced for pain management. Thus, the present study was performed to evaluate the pain alleviating effect of intrathecal injection of different doses of muscimol as GABAA receptor agonist in spinal cord injury (SCI) model of neuropathic pain. Methods: In the present experimental study male Wistar rats were treated by muscimol 0.01, 0.1 or 1 µg/10ul, intrathecally (i.t.) three weeks after induction of spinal cord injury using compression injury model. Neuropathic pain symptoms were assessed at before treatment, 15 minutes, one hour and three hours after muscimol administration. The time of peak effect and optimum dosage was assessed by repeated measures analysis of variance and analysis of covariance, respectively. Results: Muscimol with the dose of 0.01 µg in 15 minutes caused to improve the thermal hyperalgesia (df: 24, 5; F= 6.6; p<0.001), mechanical hyperalgesia (df: 24, 5; F= 7.8; p<0.001), cold allodynia (df: 24, 5; F= 6.96; p<0.001), and mechanical allodynia (df: 24, 5; F= 15.7; p<0.001). The effect of doses of 0.1 µg and 1 µg were also significant. In addition, the efficacy of different doses of muscimol didn't have difference on thermal hyperalgesia (df: 24, 5; F= 1.52; p= 0.24), mechanical hyperalgesia (df: 24, 5; F= 0.3; p= -0.75), cold allodynia (df: 24, 5; F= 0.8; p= -0.56), and mechanical allodynia (df: 24, 5; F= 1.75; p= 0.86). Conclusion: The finding of the present study revealed that using muscimol with doses of 0.01µg, 0.1µg, and 1 µg reduces the symptoms of neuropathic pain. Also the effect of GABAA agonist is short term and its effectiveness gradually decreases by time.